Teaching English Online During the National Lockdown: Students’ Perceptions and Experiences at a Spanish University - Echauri Galván, Bruno; García Hernández, Silvia; Fernández-Gil, María Jesús (Íkala, Revista de Lenguaje y Cultura, 2021)
The outbreak of the covid-19 pandemic in Spain was a major challenge for universities offering face-to-face education since these were compelled to adjust to online teaching in an extremely brief time span. This article aims to offer a comprehensive picture of the repercussions that such a sudden immersion in full virtual mode had on instrumental English subjects taught in different undergraduate programs at Universidad de Alcalá in Spain. The profile is based on the data collected from: (a) a survey with 159 respondents enrolled in English courses in the faculties of Philosophy and Arts, and of Economics, Business and Tourism; and (b) a subsequent discussion group, including the authors of the study and a deliberately selected number of respondents. Both methods were used to delve into core aspects of language teaching such as: (a) skills acquisition, (b) assessment methods, (c) the usefulness of the ict tools employed in the classroom, or in-class, and (d) interactions between students and between students and teachers in this exceptional context of unforeseen remote education. Results underscore the problems this scenario entails for the practice and acquisition of skills such as oral performance, class participation, or the management of teamwork and interpersonal relationships. They also pinpoint certain benefits related to an enhanced knowledge and handling of ict tools. Finally, they give instructors insight into the digital applications and assessment instruments which were more and less highly valued by students.